Clinical Outcomes of Multi‐Hole Covered Self‐Expandable Metal Stents for Malignant Distal Biliary Obstruction: A Retrospective Comparative Study With an Exploratory Evaluation of 6‐mm Devices - Akinobu Koiwai; Yuki Miyashita; Nana Inomata; Takehito Ito; Morihisa Hirota; Kennichi Satoh (DEN Open, 2027)
ABSTRACT Objectives Covered self‐expandable metal stents (CSEMS) are widely used for malignant distal biliary obstruction (MDBO), but cholecystitis, post‐endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP), stent migration, and recurrent biliary obstruction (RBO) remain clinically important limitations. Multi‐hole SEMS (MHSEMS) is a novel CSEMS designed to preserve side‐branch drainage and reduce migration. We evaluated MHSEMS compared with conventional CSEMS and explored the potential impact of a newly available 6‐mm MHSEMS. Methods This retrospective single‐center study included consecutive patients who underwent initial transpapillary SEMS placement for MDBO between September 2015 and December 2025. Study‐I compared MHSEMS versus conventional CSEMS limited to 8–10 mm diameter stents. Study‐II included MHSEMS cases only and compared 6‐mm versus 8–10 mm MHSEMS. Outcomes included cholecystitis, PEP, RBO, time to RBO (TRBO), and RBO causes. Results Study‐I included 148 patients; median follow‐up was 80.5 versus 81.5 days ( p = 0.761). Overall cholecystitis was 1/34 versus 23/98 ( p = 0.008). MHSEMS was independently protective for cholecystitis (odds ratio [OR] 0.0879; 95% confidence interval [95%CI] 0.0111–0.696), whereas cystic duct involvement increased risk (OR 3.190; 95%CI 1.160–8.720). PEP was 4/36 versus 18/112 ( p = 0.595). RBO was 1/36 versus 28/112, including migration in 0 versus 9. TRBO was longer with MHSEMS (log‐rank p = 0.023). Study‐II included 64 MHSEMS cases; PEP was 1/28 versus 4/36 ( p = 0.375), RBO was 1/28 versus 1/36, and no migration occurred. Conclusions MHSEMS was associated with fewer cholecystitis events and migration and longer TRBO versus conventional CSEMS. The potential benefit of 6‐mm MHSEMS for reducing PEP remains exploratory and requires confirmation in longer prospective studies.